Low Tannins and HCN of Lindur Fruit Flour Products as an Alternative Food - sulistyawati, Sulistyawati; Wignyanto, Wignyanto; Kumalaningsih, Sri (Fakultas Teknologi Pertanian Universitas Brawijaya, 2012)
Lindur fruit (Bruguiera gymnorrhiza Lamk.) has opportunities to be explored as an alternative food because it contains high carbohydrate that can be processed into flour. Lindur fruits contain antinutrient, namely tannin and Hydrogen Cyanide (HCN) that of which concentration should be reduced first before processing to be safe for consumption. This study aims to determine the concentration of rice husk ash and the right soaking time to decrease the level of tannins and HCN of the lindur fruit flour into safe limits level for consumption. This research used Randomized Group Design with two factors, namely rice husk ash concentration (20, 25, 30% w/w) and immersion time (12, 24, 36 hours). Analysis of Variance was used as Statistical data analysis of the research. Duncan Multiple Range Test on the level of sygnificancy 1% was used to test the different among treatment. The result shown that soaking lindur fruit at the concentration 30% w/w of husk ash solution in 24 hours can be reduced anti-nutrient substance to the safe limit for consumption, with the remaining tannin levels at 0.206% and 3.435 ppm of HCN. Lindur fruit drying to be processed into flour used temperature of 70 0C can reduced moisture content of 8.468% in 10 hours and produced the flour which meet the requirements as a brownish color food; 96.271% absorption of water; yield at 18.940%; 82.092% of carbohydrate; 5.597% of protein; 1.797% of fat; 18.476% of amylose; 8.701% of crude fiber; 1.609% of ash; 0.192% of tannins and 3.375 ppm of HCN. Keywords: mangrove, rice husk ash, soaking, drying temperatur